The study of photocatalytic activity of synthesized Ag/WO3 composite under visible light irradiation - Li, Jing Xiong (2015)
As one of the major concern worldwide, water pollution has been brought up as top issues to focus on. Here we investigated that Ag-doped WO3 under light irradiation showed great effect in degrading organic pollutant and disinfection. In this project, after the synthesis process of WO3 and Ag/WO3, experiments were carried out to study the photo-catalytic activity of WO3 and Ag-doped WO3 composites. By applying photo-reduction method, Ag can be anchored onto the surface of WO3 nanoplate. Subsequently, series of characterization were adopted such as Transmission electron microscopy (TEM), X-ray diffraction (XRD), Brunauer-Emmett-Teller (BET), and UV-vis diffuse reflectance spectroscopy to study the structure and character of the target material. In the degradation experiment, Sulfanilamide (SNM) was chosen as the target pollutant. It was treated under light exposure by different samples of Ag/WO3 as well as pure WO3. The results showed that the composite material performed better in degradation under irradiation compare to pure WO3. The sample that was synthesized under the condition of 2h irradiation and 180 degree had the best performance. Also, in the test of antibacterial activity, Ag ions emitted from the metal Ag contributed to enhance the efficiency of bacteria removal by attacking the cell membrane to kill the bacteria.